THE EFFECT OF PRINCIPALS’ VISIONARY LEADERSHIP STYLE AND TEACHERS’ WORK MOTIVATION ON THE ACCOUNTING TEACHERS’ READINESS IN FACING CURICULLUM CHANGES WITH THE ORGANIZATIONAL CULTURE AS MODERATING VARIABLE - Marsha Tabarruj Albir Nurut; Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2016)
It is a causal comparative research aimed to know : (1) The effect of Principals Visionary Leadership Style on the Teachers Readiness in facing Curriculum Change; (2) The effect of Teachers Work Motivation on the Teachers Readiness in facing Curriculum Change; (3) The effect of Principals Visionary Leadership Style on the Teachers Readiness in Facing Curriculum Change with the Organizational Culture as moderating variable; (4) The effect of Teacher Work Motivation on the Teachers Readiness in Facing Curriculum Change with the Organizational Culture as moderating variable. The research population was Accounting Teachers in three private Vocational High Schools (SMK) in Magelang. Data gathering was conducted through questionnaire distribution using census method. The classical assumption test covered linearity test, multicollinearity test and heterokesdasticity test. Data analysis technique used Simple Linear Regression and Moderated Regression Analysis (MRA). The research results showed that (1) Principals Visionary Leadership Style positively influenced Teachers Readiness in Facing Curriculum Change shown by value r(xly) of 0.742, value r2(xly) of 0.550, significant value was 0.000; (2) Teachers Work Motivation positively influenced Teachers Readiness in Facing Curriculum Change shown by r(x2y) of 0.731, value r2(x2y) of 0.535, significant value was 0.000; (3) Organizational Culture could not moderate the influence of Principals Visionary Leadership Style on the Teachers Readiness in facing Curriculum Change shown by equation Y = -12.284 + 1.184X1 + 1.123Z – 0.012X1*Z and the significant value of 0.653; and (4) Organizational Culture could not moderate the influence of Teachers Work Motivation on the Teachers Readiness in facing Curriculum Change shown by an equation Y = -36.197 + 1.559X2 + 1.937Z – 0.028X2*Z and significant value of 0.163.Keywords: Principals Visionary Leadership Style, Teachers Work Motivation, Teachers Readiness in Facing Curriculum Change, Organizational Culture